Supramolecular discrimination and diagnosis-guided treatment of intracellular bacteria - Jia-Hong Tian; Siyuan Huang; Ze-Han Wang; Juan-Juan Li; Xianhui Song; Ze-Tao Jiang; Bing-Sen Shi; Ying-Ying Zhao; Hui-Yan Zhang; Ke-Rang Wang; Xin-Yue Hu; Xinge Zhang; et al. (Nature Communications)
Abstract Pathogenic intracellular bacteria pose a significant threat to global public health due to the barriers presented by host cells hindering the timely detection of hidden bacteria and the effective delivery of therapeutic agents. To address these challenges, we propose a tandem diagnosis-guided treatment paradigm. A supramolecular sensor array is developed for simple, rapid, accurate, and high-throughput identification of intracellular bacteria. This diagnostic approach executes the significant guiding missions of screening a customized host-guest drug delivery system by disclosing the rationale behind the discrimination. We design eight azocalix[4]arenes with differential active targeting, cellular internalization, and hypoxia responsiveness to penetrate cells and interact with bacteria. Loaded with fluorescent indicators, these azocalix[4]arenes form a sensor array capable of discriminating eight intracellular bacterial species without cell lysis or separation. By fingerprinting specimens collected from bacteria-infected mice, the facilitated accurate diagnosis offers valuable guidance for selecting appropriate antibiotics. Moreover, mannose-modified azocalix[4]arene (ManAC4A) is screened as a drug carrier efficiently taken up by macrophages. Doxycycline loaded with ManAC4A exhibits improved efficacy against methicillin-resistant Staphylococcus aureus-infected peritonitis. This study introduces an emerging paradigm to intracellular bacterial diagnosis and treatment, offering broad potential in combating bacterial infectious diseases.